2015
DOI: 10.1038/srep10986
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of genital human papillomavirus infection in couples: a population-based cohort study in rural China

Abstract: HPV transmission dynamics have rarely been studied in the general population, especially in China. We followed the genital HPV infection status of both partners in 874 couples aged 25-65 years from rural China for up to 7 bi-annual visits during 2009-2013. The positive HPV concordance and transmission rate for partners in a couple were evaluated and relevant risk factors were assessed. The concordance of any, oncogenic, and non-oncogenic HPV was 15.52%, 16.18% and 10.41%, respectively. Male-to-female transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…However, our study shown that the risk of HPV infection increases in women as the husband's age increases. In a previous study, the male‐to‐female transmission risk for oncogenic mucosal HPV was significantly higher than the female‐to‐male transmission risk . Worldwide, the prevalence of genital HPV varies depending on region and population source, ranging from 14% to > 90% in women and from 1.3% to 72.9% in men .…”
Section: Discussionmentioning
confidence: 85%
“…However, our study shown that the risk of HPV infection increases in women as the husband's age increases. In a previous study, the male‐to‐female transmission risk for oncogenic mucosal HPV was significantly higher than the female‐to‐male transmission risk . Worldwide, the prevalence of genital HPV varies depending on region and population source, ranging from 14% to > 90% in women and from 1.3% to 72.9% in men .…”
Section: Discussionmentioning
confidence: 85%
“…Transmission from man to woman or woman to man has been evaluated in six of the recent studies shown in Table 1. Three of the studies have detected that transmission of α-HPV occurs more likely from man to woman [4, 19, 20] and two from woman to man [16, 17]. The only study detecting β- and γ-HPV infection within a 6-week follow-up, so far, has not found any difference in transmission between sexes [6].…”
Section: Hpv Transmission In Heterosexual Couplesmentioning
confidence: 99%
“…In addition to actual transmission studies, cervical HPV infection in a man’s female sexual partner has been found to be a risk for the man’s genital HPV infection [24]. Other risk factors for type-specific concordance were (1) an increasing number of younger couples, (2) persistent HPV infection, (3) higher frequency of sexual intercourse, (4) rising number of spouse’s lifetime sexual partners, as well as (5) sexual relations with prostitutes [9, 14, 19, 25]. A recent systematic review evaluated the risk of cancer among spouses of patients with HPV-related cancer [25].…”
Section: Risk Factors For Hpv Concordance In Heterosexual Couplesmentioning
confidence: 99%
“…3, 4 Recently, a cohort study conducted in heterosexual couples illustrated that the male-to-female and female-to-male HPV transmission rates were 7.11 and 5.56 per 1000 person months, respectively. 5 Therefore, the epidemiological characterization of HPV infection in both sexes from the same population is important to understand the whole picture of HPV transmission and natural history in humans.…”
Section: Introductionmentioning
confidence: 99%